Building reliable supply chains for noncommunicable disease commodities: lessons learned from HIV and evidence needs. (1st July 2018) - Pastakia, Sonak D.; Tran, Dan N.; Manji, Imran; Wells, Cassia; Kinderknecht, Kyle; Ferris, Robert
Abstract : Objective: Successful noncommunicable disease (NCD) management requires a reliable supply chain. The objectives of this article are to examine lessons learned from HIV supply chain initiatives, describe opportunities to advance supply chain systems for NCD health commodities based on HIV supply chain successes and identify areas where additional research is still needed for reliable NCD supply chains in LMICs. Design: We describe practical experiences gained from developing HIV supply chain systems and how those lessons can be used to inform NCD supply chain systems. Methods: Supply chain challenges with HIV commodities in low and middle-income countries (LMICs) are identified and categorized using literature review and expert experiences. Solutions are described on the basis of lessons learned from global HIV initiatives. Opportunities to further advance NCD supply chain systems are recommended. Results: Supply chain challenges can be organized into two groups: 1) resource mobilization and 2) resource utilization. Global HIV initiatives have responded to resource mobilization challenges by increasing availability of funding, filling human resource gaps, improving essential storage and creating better transport mechanisms and information technology infrastructure. These initiatives have assisted in better resource utilization by strengthening procurement processes, standardizing and simplifying supply chain systems, reducing integrity and security vulnerabilities and harnessing the power of better data. Advances achieved through HIV initiatives are readily transferrable to NCD supply chains with minimal additional investment. Research opportunities exist to identify the most efficient and cost-effective ways to develop more reliable supply chains for NCDs.